'Just another policy document?' Can a protocol end the criminalisation of kids in care?. (March 2019) - McFarlane, Kath; Colvin, Emma; McGrath, Andrew; Gerard, Alison
This article examines the New South Wales Joint Protocol to Reduce the Contact of Young People in Residential OOHC with the Criminal Justice System (2016 ) from the perspective of residential out-of-home-care providers, police, lawyers and departmental staff involved in the child welfare and criminal justice systems in New South Wales.